Methane Emissions from Unique Wetlands in China: Case Studies, Meta Analyses and Modelling - Chen, Huai; Wu, Ning; Peng, Changhui; Wang, Yanfen (DE GRUYTER, 2015)

Methane Fluxes from Alpine Wetlands of Zoige Plateau in Relation to Water Regime and Vegetation under Two Scales - Chen, Huai; Wu, Ning; Wang, Yanfen; Gao, Yongheng; Peng, Changhui (Water, Air, & Soil Pollution, 2011)

From plant functional types to plant functional traits: A new paradigm in modelling global vegetation dynamics - Yang, Yanzheng; Zhu, Qiuan; Peng, Changhui; Wang, Han; Chen, Huai (Progress in Physical Geography: Earth and Environment, 2015)
Dynamic global vegetation models (DGVMs) typically track the material and energy cycles in ecosystems with finite plant functional types (PFTs). Increasingly, the community ecology and modelling studies recognize that current PFT scheme is not sufficient for simulating ecological processes. Recent advances in the study of plant functional traits (FTs) in community ecology provide a novel and feasible approach for the improvement of PFT-based DGVMs. This paper reviews the development of current DGVMs over recent decades. After characterizing the advantages and disadvantages of the PFT-based scheme, it summarizes trait-based theories and discusses the possibility of incorporating FTs into DGVMs. More importantly, this paper summarizes three strategies for constructing next-generation DGVMs with FTs. Finally, the method’s limitations, current challenges and future research directions for FT theory are discussed for FT theory. We strongly recommend the inclusion of several FTs, namely specific leaf area (SLA), leaf nitrogen content (LNC), carbon isotope composition of leaves (Leaf δ 13 C), the ratio between leaf-internal and ambient mole fractions of CO 2 (Leaf C i /C a ), seed mass and plant height. These are identified as the most important in constructing DGVMs based on FTs, which are also recognized as important ecological strategies for plants. The integration of FTs into dynamic vegetation models is a critical step towards improving the results of DGVM simulations; communication and cooperation among ecologists and modellers is equally important for the development of the next generation of DGVMs.

Delayed spring phenology on the Tibetan Plateau may also be attributable to other factors than winter and spring warming - Chen, Huai; Zhu, Qiuan; Wu, Ning; Wang, Yanfen; Peng, Chang-Hui (Proceedings of the National Academy of Sciences, 2011)

Effects of canopy gaps on N 2 O fluxes in a tropical montane rainforest in Hainan of China - Yang, Huai; Detto, Matteo; Liu, Shirong; Yuan, Wenping; Hsieh, Cheng-I; Wang, Xu; Chen, Renli; Chen, Huai; Peng, Changhui; Jiang, Xinhua; Li, Yide; Xu, Han; et al. (Ecological Engineering, 2017)

Large-scale detection of vegetation dynamics and their potential drivers using MODIS images and BFAST: A case study in Quebec, Canada - Fang, Xiuqin; Zhu, Qiuan; Ren, Liliang; Chen, Huai; Wang, Kai; Peng, Changhui (Remote Sensing of Environment, 2018)

Eco-CCUS: A cost-effective pathway towards carbon neutrality in China - Li, Mingxu; He, Nianpeng; Xu, Li; Peng, Changhui; Chen, Huai; Yu, Guirui (Renewable and Sustainable Energy Reviews, 2023)

Quantification of methane emissions from municipal solid waste landfills in China during the past decade - Du, Mingxi; Peng, Changhui; Wang, Xiaoge; Chen, Huai; Wang, Meng; Zhu, Qiuan (Renewable and Sustainable Energy Reviews, 2017)

Temporal and Spatial Variation of Wetland CH4 Emissions from the Qinghai–Tibet Plateau under Future Climate Change Scenarios - Zhang, Xian; Wang, Jieyi; Zhang, Jiang; Chen, Huai; Peng, Changhui; Zhu, Qiuan (Atmosphere, 2022)
Wetlands are an important natural source of methane (CH4), so it is important to quantify how their emissions may vary under future climate change conditions. The Qinghai–Tibet Plateau contains more than a third of China’s wetlands. Here, we simulated temporal and spatial variation in CH4 emissions from natural wetlands on the Qinghai–Tibet Plateau from 2008 to 2100 under Representative Concentration Pathways (RCP) 2.6, 4.5, and 8.5. Based on the simulation results of the TRIPLEX-GHG model forced with data from 24 CMIP5 models of global climate, we predict that, assuming no change in wetland distribution on the Plateau, CH4 emissions from natural wetlands will increase by 35%, 98% and 267%, respectively, under RCP 2.6, 4.5 and 8.5. The predicted increase in atmospheric CO2 concentration will contribute 10–28% to the increased CH4 emissions from wetlands on the Plateau by 2100. Emissions are predicted to be majorly in the range of 0 to 30.5 g C m−2·a−1 across the Plateau and higher from wetlands in the southern region of the Plateau than from wetlands in central or northern regions. Under RCP8.5, the methane emissions of natural wetlands on the Qinghai–Tibet Plateau increased much more significantly than that under RCP2.6 and RCP4.5.

Assessing the spatio-temporal variation and uncertainty patterns of historical and future projected water resources in China - Zhu, Qiuan; Jiang, Hong; Peng, Changhui; Liu, Jinxun; Fang, Xiuqin; Chen, Huai; Liu, Shirong (Journal of Water and Climate Change, 2013)
The spatial and temporal variation and uncertainty of precipitation and runoff in China were compared and evaluated between historical and future periods under different climate change scenarios. The precipitation pattern is derived from observed and future projected precipitation data for historical and future periods, respectively. The runoff is derived from simulation results in historical and future periods using a dynamic global vegetation model (DGVM) forced with historical observed and global climate models (GCMs) future projected climate data, respectively. One GCM (CGCM3.1) under two emission scenarios (SRES A2 and SRES B1) was used for the future period simulations. The results indicated high uncertainties and variations in climate change effects on hydrological processes in China: precipitation and runoff showed a significant increasing trend in the future period but a decreasing trend in the historical period at the national level; the temporal variation and uncertainty of projected precipitation and runoff in the future period were predicted to be higher than those in the historical period; the levels of precipitation and runoff in the future period were higher than those in the historical period. The change in trends of precipitation and runoff are highly affected by different climate change scenarios. GCM structure and emission scenarios should be the major sources of uncertainty.

Nitrous oxide fluxes from the littoral zone of a lake on the Qinghai-Tibetan Plateau - Chen, Huai; Wang, Meng; Wu, Ning; Wang, Yanfen; Zhu, Dan; Gao, Yongheng; Peng, Changhui (Environmental Monitoring and Assessment, 2011)

A novel pathway of direct methane production and emission by eukaryotes including plants, animals and fungi: An overview - Liu, Jiangong; Chen, Huai; Zhu, Qiuan; Shen, Yan; Wang, Xue; Wang, Meng; Peng, Changhui (Atmospheric Environment, 2015)

Nitrous oxide fluxes from three forest types of the tropical mountain rainforests on Hainan Island, China - Bai, Zhenzhi; Yang, Gang; Chen, Huai; Zhu, Qiuan; Chen, Dexiang; Li, Yide; Wang, Xu; Wu, Zhongmin; Zhou, Guangyi; Peng, Changhui (Atmospheric Environment, 2014)

Methane emissions from the surface of the Three Gorges Reservoir: CH_4 EMISSIONS FROM TGR - Chen, Huai; Yuan, Xingzhong; Chen, Zhongli; Wu, Yuyuan; Liu, Xianshu; Zhu, Dan; Wu, Ning; Zhu, Qiu'an; Peng, Changhui; Li, Weizhong (Journal of Geophysical Research: Atmospheres, 2011)

Structural and functional differentiation of the microbial community in the surface and subsurface peat of two minerotrophic fens in China - Wang, Meng; Tian, Jianqing; Bu, Zhaojun; Lamit, Louis J.; Chen, Huai; Zhu, Qiuan; Peng, Changhui (Plant and Soil, 2019)

CH4 concentrations and fluxes in a subtropical metropolitan river network: Watershed urbanization impacts and environmental controls - Wang, Xiaofeng; He, Yixin; Chen, Huai; Yuan, Xingzhong; Peng, Changhui; Yue, Junsheng; Zhang, Qiaoyong; Zhou, Lilei (Science of The Total Environment, 2018)

Estimating global natural wetland methane emissions using process modelling: spatio‐temporal patterns and contributions to atmospheric methane fluctuations - Zhu, Qiuan; Peng, Changhui; Chen, Huai; Fang, Xiuqin; Liu, Jinxun; Jiang, Hong; Yang, Yanzheng; Yang, Gang (Global Ecology and Biogeography, 2015)
Abstract Aim The fluctuations of atmospheric methane ( CH 4 ) that have occurred in recent decades are not fully understood, particularly with regard to the contribution from wetlands. The application of spatially explicit parameters has been suggested as an effective method for reducing uncertainties in bottom‐up approaches to wetland CH 4 emissions, but has not been included in recent studies. Our goal was to estimate spatio‐temporal patterns of global wetland CH 4 emissions using a process model and then to identify the contribution of wetland emissions to atmospheric CH 4 fluctuations. Location Global. Methods A process‐based model integrated with full descriptions of methanogenesis ( TRIPLEX‐GHG ) was used to simulate global wetland CH 4 emissions. Results Global annual wetland CH 4 emissions ranged from 209 to 245 T g CH 4 year −1 between 1901 and 2012, with peaks occurring in 1991 and 2012. There is a decreasing trend between 1990 and 2010 with a rate of approximately 0.48 T g CH 4 year −1 , which was largely caused by emissions from tropical wetlands showing a decreasing trend of 0.44 T g CH 4 year −1 since the 1970s. Emissions from tropical, temperate and high‐latitude wetlands comprised 59, 26 and 15% of global emissions, respectively. Main conclusion Global wetland CH 4 emissions, the interannual variability of which was primary controlled by tropical wetlands, partially drive the atmospheric CH 4 burden. The stable to decreasing trend in wetland CH 4 emissions, a result of a balance of emissions from tropical and extratropical wetlands, was a particular factor in slowing the atmospheric CH 4 growth rate during the 1990s. The rapid decrease in tropical wetland CH 4 emissions that began in 2000 was supposed to offset the increase in anthropogenic emissions and resulted in a relatively stable level of atmospheric CH 4 from 2000 to 2006. Increasing wetland CH 4 emissions, particularly after 2010, should be an important contributor to the growth in atmospheric CH 4 seen since 2007.

Monitoring the impact of aerosol contamination on the drought-induced decline of gross primary productivity - Zhang, Yao; Li, Weizhong; Zhu, Qiuan; Chen, Huai; Fang, Xiuqin; Zhang, Tinglong; Zhao, Pengxiang; Peng, Changhui (International Journal of Applied Earth Observation and Geoinformation, 2015)

Analysis of vegetation dynamics and climatic variability impacts on greenness across Canada using remotely sensed data from 2000 to 2009 - Fang, Xiuqin; Zhu, Qiuan; Chen, Huai; Ma, Zhihai; Wang, Weifeng; Song, Xinzhang; Zhao, Pengxiang; Peng, Changhui (Journal of Applied Remote Sensing, 2014)

Monitoring and estimating drought-induced impacts on forest structure, growth, function, and ecosystem services using remote-sensing data: recent progress and future challenges - Zhang, Yao; Peng, Changhui; Li, Weizhong; Fang, Xiuqin; Zhang, Tinglong; Zhu, Qiuan; Chen, Huai; Zhao, Pengxiang (Environmental Reviews, 2013)
Alongside global warming, droughts are expected to increase in frequency, severity, and extent in the near future, which will likely result in significant impacts on forest growth, production, structure, composition, and ecosystem services. However, due to spatial and temporal characteristics, it is difficult to monitor and assess the potential effects of droughts. Remote sensing can provide an effective way to obtain real-time conditions of forests affected by drought and offer a range of spatial and temporal insights into drought-induced changes to forest ecosystem structure, function, and services. Remote sensing is rapidly developing as more satellites are launched. In situ and remotely sensed data fusion techniques have achieved notable success in assessing drought-induced damage to forests and carbon cycles. Even so, constraints still exist when using satellite data. The objectives of this review are to (1) briefly review existing data sources and methods of remote sensing; (2) synthesize current applications and contributions of remote sensing in monitoring and estimating impacts of droughts on forest ecosystems; and (3) highlight research gaps and future challenges.

High uncertainties detected in the wetlands distribution of the Qinghai–Tibet Plateau based on multisource data - Wang, Jieyi; Zhu, Qiuan; Yang, Yan; Zhang, Xian; Zhang, Jiang; Yuan, Minshu; Chen, Huai; Peng, Changhui (Landscape and Ecological Engineering, 2020)

Estimating soil organic carbon redistribution in three major river basins of China based on erosion processes - Yang, Yan; Zhu, Qiuan; Liu, Jinxun; Li, Mingxu; Yuan, Minshu; Chen, Huai; Peng, Changhui; Yang, Zhenan (Soil Research, 2020)
Soil erosion by water affects soil organic carbon (SOC) migration and distribution, which are important processes for defining ecosystem carbon sources and sinks. Little has been done to quantify soil carbon erosion in the three major basins in China, the Yangtze River, Yellow River and Pearl River Basins, which contain the most eroded areas. This research attempts to quantify the lateral movement of SOC based on spatial and temporal patterns of water erosion rates derived from an empirical Unit Stream Power Erosion Deposition Model (USPED) model. The water erosion rates simulated by the USPED model agreed reasonably with observations (R2 = 0.43, P < 0.01). We showed that regional water erosion ranged within 23.3–50 Mg ha–1 year–1 during 1992–2013, inducing the lateral redistribution of SOC caused by erosion in the range of 0.027–0.049 Mg C ha–1 year–1, and that caused by deposition of 0.0079–0.015 Mg C ha–1 year–1, in the three basins. The total eroded SOC was 0.006, 0.002 and 0.001 Pg year–1 in the Yangtze River, Yellow River and Pearl River Basins respectively. The net eroded SOC in the three basins was ~0.0075 Pg C year–1. Overall, the annual average redistributed SOC rate caused by erosion was greater than that caused by deposition, and the SOC loss in the Yangtze River Basin was greatest among the three basins. Our study suggests that considering both processes of erosion and deposition – as well as effects of topography, rainfall, land use types and their interactions – on these processes are important to understand SOC redistribution caused by water erosion.

Assessment of frozen ground organic carbon pool on the Qinghai-Tibet Plateau - Jiang, Lin; Chen, Huai; Zhu, Qiuan; Yang, Yanzheng; Li, Mingxu; Peng, Changhui; Zhu, Dan; He, Yixin (Journal of Soils and Sediments, 2019)

An optimized water table depth detected for mitigating global warming potential of greenhouse gas emissions in wetland of Qinghai-Tibetan Plateau - Zhang, Jiang; Chen, Huai; Wang, Meng; Liu, Xinwei; Peng, Changhui; Wang, Le; Yu, Dongxue; Zhu, Qiuan (iScience, 2024)

Responses of soil CH4 fluxes to nitrogen addition in two tropical montane rainforests in southern China - Wu, Fangtao; Peng, Changhui; Wang, Chuanyao; Chen, Huai; Liu, Weiguo; Liu, Zhihao; Wang, Hui; Li, Hong; Chen, Dexiang; Li, Yide; Liu, Shirong (Forest Ecosystems, 2022)

Quantification of Ecosystem-Scale Methane Sinks Observed in a Tropical Rainforest in Hainan, China - Liu, Zhihao; Li, Hong; Wu, Fangtao; Wang, Hui; Chen, Huai; Zhu, Qiuan; Yang, Gang; Liu, Weiguo; Chen, Dexiang; Li, Yide; Peng, Changhui (Land, 2022)
Tropical rainforest ecosystems are important when considering the global methane (CH4) budget and in climate change mitigation. However, there is a lack of direct and year-round observations of ecosystem-scale CH4 fluxes from tropical rainforest ecosystems. In this study, we examined the temporal variations in CH4 flux at the ecosystem scale and its annual budget and environmental controlling factors in a tropical rainforest of Hainan Island, China, using 3 years of continuous eddy covariance measurements from 2016 to 2018. Our results show that CH4 uptake generally occurred in this tropical rainforest, where strong CH4 uptake occurred in the daytime, and a weak CH4 uptake occurred at night with a mean daily CH4 flux of −4.5 nmol m−2 s−1. In this rainforest, the mean annual budget of CH4 for the 3 years was −1260 mg CH4 m−2 year−1. Furthermore, the daily averaged CH4 flux was not distinctly different between the dry season and wet season. Sixty-nine percent of the total variance in the daily CH4 flux could be explained by the artificial neural network (ANN) model, with a combination of air temperature (Tair), latent heat flux (LE), soil volumetric water content (VWC), atmospheric pressure (Pa), and soil temperature at −10 cm (Tsoil), although the linear correlation between the daily CH4 flux and any of these individual variables was relatively low. This indicates that CH4 uptake in tropical rainforests is controlled by multiple environmental factors and that their relationships are nonlinear. Our findings also suggest that tropical rainforests in China acted as a CH4 sink during 2016–2018, helping to counteract global warming.

Nitrous oxide emission from infralittoral zone and pelagic zone in a shallow lake: Implications for whole lake flux estimation and lake restoration - Zhu, Dan; Wu, Yan; Wu, Ning; Chen, Huai; He, Yixin; Zhang, Yongmei; Peng, Changhui; Zhu, Qiu'an (Ecological Engineering, 2015)

Carbon accumulation and sequestration of lakes in China during the Holocene - Wang, Mei; Chen, Huai; Yu, Zicheng; Wu, Jianghua; Zhu, Qiu'an; Peng, Changhui; Wang, Yanfen; Qin, Boqiang (Global Change Biology, 2015)
Abstract Understanding the responses of lake systems to past climate change and human activity is critical for assessing and predicting the fate of lake carbon (C) in the future. In this study, we synthesized records of the sediment accumulation from 82 lakes and of C sequestration from 58 lakes with direct organic C measurements throughout China. We also identified the controlling factors of the long‐term sediment and C accumulation dynamics in these lakes during the past 12 ka (1 ka = 1000 cal yr BP ). Our results indicated an overall increasing trend of sediment and C accumulation since 12 ka, with an accumulation peak in the last couple of millennia for lakes in China, corresponding to terrestrial organic matter input due to land‐use change. The Holocene lake sediment accumulation rate ( SAR ) and C accumulation rate ( CAR ) averaged (mean ± SE ) 0.47 ± 0.05 mm yr −1 and 7.7 ± 1.4 g C m −2 yr −1 in China, respectively, comparable to the previous estimates for boreal and temperate regions. The SAR for lakes in the East Plain of subtropical China (1.05 ± 0.28 mm yr −1 ) was higher than those in other regions ( P < 0.05). However, CAR did not vary significantly among regions. Overall, the variability and history of climate and anthropogenic interference regulated the temporal and spatial dynamics of sediment and C sequestration for lakes in China. We estimated the total amount of C burial in lakes of China as 8.0 ± 1.0 Pg C. This first estimation of total C storage and dynamics in lakes of China confirms the importance of lakes in land C budget in monsoon‐influenced regions.

Relationship between Air Pollutants and Economic Development of the Provincial Capital Cities in China during the Past Decade - Luo, Yunpeng; Chen, Huai; Zhu, Qiu'an; Peng, Changhui; Yang, Gang; Yang, Yanzheng; Zhang, Yao (PLoS ONE, 2014)

Eradicating invasive Spartina alterniflora with alien Sonneratia apetala and its implications for invasion controls - Chen, Huai; Liao, Baowen; Liu, Bin’er; Peng, Changhui; Zhang, Yao; Guan, Wei; Zhu, Qiu’an; Yang, Gang (Ecological Engineering, 2014)

Regional drought-induced reduction in the biomass carbon sink of Canada's boreal forests - Ma, Zhihai; Peng, Changhui; Zhu, Qiuan; Chen, Huai; Yu, Guirui; Li, Weizhong; Zhou, Xiaolu; Wang, Weifeng; Zhang, Wenhua (Proceedings of the National Academy of Sciences, 2012)
The boreal forests, identified as a critical “tipping element” of the Earth's climate system, play a critical role in the global carbon budget. Recent findings have suggested that terrestrial carbon sinks in northern high-latitude regions are weakening, but there has been little observational evidence to support the idea of a reduction of carbon sinks in northern terrestrial ecosystems. Here, we estimated changes in the biomass carbon sink of natural stands throughout Canada's boreal forests using data from long-term forest permanent sampling plots. We found that in recent decades, the rate of biomass change decreased significantly in western Canada (Alberta, Saskatchewan, and Manitoba), but there was no significant trend for eastern Canada (Ontario and Quebec). Our results revealed that recent climate change, and especially drought-induced water stress, is the dominant cause of the observed reduction in the biomass carbon sink, suggesting that western Canada's boreal forests may become net carbon sources if the climate change–induced droughts continue to intensify.

Estimates and Predictions of Methane Emissions from Wastewater in China from 2000 to 2020 - Du, Mingxi; Zhu, Qiuan; Wang, Xiaoge; Li, Peng; Yang, Bin; Chen, Huai; Wang, Meng; Zhou, Xiaolu; Peng, Changhui (Earth's Future, 2018)
Methane accounts for 20% of the global warming caused by greenhouse gases, and wastewater is a major anthropogenic source of methane. Based on the Intergovernmental Panel on Climate Change greenhouse gas inventory guidelines and current research findings, we calculated the amount of methane emissions from 2000 to 2014 that originated from wastewater from different provinces in China. Methane emissions from wastewater increased from 1349.01 to 3430.03 Gg from 2000 to 2014, and the mean annual increase was 167.69 Gg. The methane emissions from industrial wastewater treated by wastewater treatment plants ( E It ) accounted for the highest proportion of emissions. We also estimated the future trend of industrial wastewater methane emissions using the artificial neural network model. A comparison of the emissions for the years 2020, 2010, and 2000 showed an increasing trend in methane emissions in China and a spatial transition of industrial wastewater emissions from eastern and southern regions to central and southwestern regions and from coastal regions to inland regions. These changes were caused by changes in economics, demographics, and relevant policies. , Key Points Methane emission from wastewater from 2000 to 2014 was calculated to increase from 1349.01 Gg to 3430.03 Gg. Methane emission from wastewater from 2015 to 2020 was estimated to increase from 3875.30 Gg to 5212.75 Gg. A spatial transition of methane emission from wastewater was found and discussed in the present study.

Global responses of wetland methane emissions to extreme temperature and precipitation - Xu, Min; Zhang, Jiang; Zhang, Zhen; Wang, Meng; Chen, Huai; Peng, Changhui; Yu, Dongxue; Zhan, Hao; Zhu, Qiuan (Environmental Research, 2024)

Spatiotemporal Variations in Nitrous Oxide Emissions from an Open Fen on the Qinghai–Tibetan Plateau: a 3-Year Study - Chen, Huai; Wang, Yanfen; Wu, Ning; Zhu, Dan; Li, Wei; Gao, Yongheng; Zhu, Qiu’an; Yang, Gang; Peng, Changhui (Water, Air, & Soil Pollution, 2012)

Soil Carbon Dioxide Fluxes from Three Forest Types of the Tropical Montane Rainforest on Hainan Island, China - Jiang, Xinhua; Chen, Huai; Peng, Changhui; Li, Yide; He, Yixin; Chen, Dexiang; Lin, Mingxian; Hu, Ji; Ma, Tianli; Liu, Liangfeng; Liu, Xinwei; Xia, Miao; et al. (Water, Air, & Soil Pollution, 2016)

A drought-induced pervasive increase in tree mortality across Canada's boreal forests - Peng, Changhui; Ma, Zhihai; Lei, Xiangdong; Zhu, Qiuan; Chen, Huai; Wang, Weifeng; Liu, Shirong; Li, Weizhong; Fang, Xiuqin; Zhou, Xiaolu (Nature Climate Change, 2011)

Global estimates of forest soil methane flux identify a temperate and tropical forest methane sink - Feng, Huili; Guo, Jiahuan; Peng, Changhui; Ma, Xuehong; Kneeshaw, Daniel; Chen, Huai; Liu, Qiuyu; Liu, Mengyao; Hu, Cheng; Wang, Weifeng (Geoderma, 2023)

Archaeal communities in the sediments of different mangrove stands at Dongzhaigang, China - Li, Wei; Guan, Wei; Chen, Huai; Liao, Baowen; Hu, Ji; Peng, Changhui; Rui, Junpeng; Tian, Jianqing; Zhu, Dan; He, Yixin (Journal of Soils and Sediments, 2016)

Effects of soil warming, rainfall reduction and water table level on CH 4 emissions from the Zoige peatland in China - Yang, Gang; Chen, Huai; Wu, Ning; Tian, Jianqing; Peng, Changhui; Zhu, Qiuan; Zhu, Dan; He, Yixin; Zheng, Qunying; Zhang, Changbing (Soil Biology and Biochemistry, 2014)

Corrigendum: Extrapolation and Uncertainty Evaluation of Carbon Dioxide and Methane Emissions in the Qinghai-Tibetan Plateau Wetlands Since the 1960s - Zhang, Jiang; Zhu, Qiuan; Yuan, Minshu; Liu, Xinwei; Chen, Huai; Peng, Changhui; Wang, Meng; Yang, Zhenan; Jiang, Lin; Zhao, Pengxiang (Frontiers in Earth Science, 2021)

Global response of terrestrial gross primary productivity to climate extremes - Yuan, Minshu; Zhu, Qiuan; Zhang, Jiang; Liu, Jinxun; Chen, Huai; Peng, Changhui; Li, Peng; Li, Mingxu; Wang, Meng; Zhao, Pengxiang (Science of The Total Environment, 2021)

Water table drawdown increases plant biodiversity and soil polyphenol in the Zoige Plateau - Zeng, Jia; Chen, Huai; Bai, Yinping; Dong, Faqin; Peng, Changhui; Yan, Fei; Cao, Qin; Yang, Zhenan; Yang, Suizhuang; Yang, Gang (Ecological Indicators, 2021)

Extrapolation and Uncertainty Evaluation of Carbon Dioxide and Methane Emissions in the Qinghai-Tibetan Plateau Wetlands Since the 1960s - Zhang, Jiang; Zhu, Qiuan; Yuan, Minshu; Liu, Xinwei; Chen, Huai; Peng, Changhui; Wang, Meng; Yang, Zhenan; Jiang, Lin; Zhao, Pengxiang (Frontiers in Earth Science, 2020)
Wetlands are important modulators of atmospheric greenhouse gas (GHGs) concentrations. However, little is known about the magnitudes and spatiotemporal patterns of GHGs fluxes in wetlands on the Qinghai-Tibetan Plateau (QTP), the world’s largest and highest plateau. In this study, we measured soil temperature and the fluxes of carbon dioxide (CO 2 ) and methane (CH 4 ) in an alpine wetland on the QTP from April 2017 to April 2019 by the static chamber method, and from January 2017 to December 2017 by the eddy covariance (EC) method. The CO 2 and CH 4 emission measurements from both methods showed different relationships to soil temperature at different timescales (annual and seasonal). Based on such relationship patterns and soil temperature data (1960–2017), we extrapolated the CO 2 and CH 4 emissions of study site for the past 57 years: the mean CO 2 emission rate was 91.38 mg C m –2 h –1 on different measurement methods and timescales, with the range of the mean emission rate from 35.10 to 146.25 mg C m –2 h –1 , while the mean CH 4 emission rate was 2.75 mg C m –2 h –1 , with the ranges of the mean emission rate from 1.41 to 3.85 mg C m –2 h –1 . The estimated regional CO 2 and CH 4 emissions from permanent wetlands on the QTP were 94.29 and 2.37 Tg C year –1 , respectively. These results indicate that uncertainties caused by measuring method and timescale should be fully considered when extrapolating wetland GHGs fluxes from local sites to the regional level. Moreover, the results of global warming potential showed that CO 2 dominates the GHG balance of wetlands on the QTP.

Effects of increasing aerosol optical depth on the gross primary productivity in China during 2000–2014 - Zhang, Jing; Ding, Juhua; Zhang, Jiang; Yuan, Minshu; Li, Peng; Xiao, Zhongyong; Peng, Changhui; Chen, Huai; Wang, Meng; Zhu, Qiuan (Ecological Indicators, 2020)

Variations of Sediment Archaea Communitiesin Different Distribution Areasof Bruguiera gymnoihiza Mangrovein Dongzhaigang, China - Li, Wei; Guan, Wei; Chen, Huai; Liao, Baowen; Hu, Ji; Rui, Junpeng; Peng, Changhui; Zhu, Dan; He, Yixin; Tian, Jianqing (Polish Journal of Environmental Studies, 2019)

Interactive Effect of Radioactive and Heavy-MetalContamination on Soil Enzyme Activityin a Former Uranium Mine - Yang, Gang; Dong, Faqin; Liu, Mingxue; Nie, Xiaoqin; Zong, Meirong; Peng, Changhui; Chen, Huai; Wei, Hongfu; Wang, Pingping; Zhang, Wei (Polish Journal of Environmental Studies, 2018)

Stable oxic-anoxic transitional interface is beneficial to retard soil carbon loss in drained peatland - Liu, Liangfeng; Tian, Jianqing; Wang, Hongjun; Xue, Dan; Huang, Xinya; Wu, Ning; Wang, Meng; Xu, Xingliang; Peng, Changhui; Wang, Yanfen; Chen, Huai (Soil Biology and Biochemistry, 2023)

Global Climate Change Increases Terrestrial Soil CH_4 Emissions - Guo, Jiahuan; Feng, Huili; Peng, Changhui; Chen, Huai; Xu, Xuan; Ma, Xuehong; Li, Li; Kneeshaw, Daniel; Ruan, Honghua; Yang, Hongqiang; Wang, Weifeng (Global Biogeochemical Cycles, 2023)
Abstract Increased greenhouse gas emissions are causing unprecedented climate change, which is, in turn, altering emissions and removals (referring to the oxidation of atmospheric CH 4 by methanotrophs within the soil) of the atmospheric CH 4 in terrestrial ecosystems. In the global CH 4 budget, wetlands are the dominant natural source and upland soils are the primary biological sink. However, it is unclear whether and how the soil CH 4 exchanges across terrestrial ecosystems and the atmosphere will be affected by warming and changes in precipitation patterns. Here, we synthesize 762 observations of in situ soil CH 4 flux data based on the chamber method from the past three decades related to temperature and precipitation changes across major terrestrial ecosystems worldwide. Our meta‐analysis reveals that warming (average warming of +2°C) promotes upland soil CH 4 uptake and wetland soil CH 4 emission. Decreased precipitation (ranging from −100% to −7% of local mean annual precipitation) stimulates upland soil CH 4 uptake. Increased precipitation (ranging from +4% to +94% of local mean annual precipitation) accelerates the upland soil CH 4 emission. By 2100, under the shared socioeconomic pathway with a high radiative forcing level (SSP585), CH 4 emissions from global terrestrial ecosystems will increase by 22.8 ± 3.6 Tg CH 4 yr −1 as an additional CH 4 source, which may be mainly attributed to the increase in precipitation over 30°N latitudes. Our meta‐analysis strongly suggests that future climate change would weaken the natural buffering ability of terrestrial ecosystems on CH 4 fluxes and thus contributes to a positive feedback spiral. , Plain Language Summary This study is the first investigation to include scenarios of CH 4 sink–source transition due to climate change and provides the global estimate of soil CH 4 budgets in natural terrestrial ecosystems in the context of climate change. The enhanced effect of climate change on CH 4 emissions was mainly attributed to increased CH 4 emissions from natural upland ecosystems. Although an increased CH 4 uptake by forest and grassland soils caused by increased temperature and decreased precipitation can offset some part of additional CH 4 sources, the substantial increase of increased precipitation on CH 4 emissions makes these sinks insignificant. These findings highlight that future climate change would weaken the natural buffering ability of terrestrial ecosystems on CH 4 emissions and thus form a positive feedback spiral between methane emissions and climate change. , Key Points This study is the first CH 4 budget investigation to include CH 4 sink‐source transition due to climate change Climate change is estimated to add 22.8 ± 3.6 Tg CH 4 yr −1 emission by 2100 under the high socioeconomic pathway Climate change weakens the buffering capacity of upland soils to CH 4 emissions

Methane emissions from rice paddies natural wetlands, lakes in China: synthesis new estimate - Chen, Huai; Zhu, Qiu'an; Peng, Changhui; Wu, Ning; Wang, Yanfen; Fang, Xiuqin; Jiang, Hong; Xiang, Wenhua; Chang, Jie; Deng, Xiangwen; Yu, Guirui (Global Change Biology, 2013)
Abstract Sources of methane ( CH 4 ) become highly variable for countries undergoing a heightened period of development due to both human activity and climate change. An urgent need therefore exists to budget key sources of CH 4 , such as wetlands (rice paddies and natural wetlands) and lakes (including reservoirs and ponds), which are sensitive to these changes. For this study, references in relation to CH 4 emissions from rice paddies, natural wetlands, and lakes in C hina were first reviewed and then reestimated based on the review itself. Total emissions from the three CH 4 sources were 11.25 Tg CH 4 yr −1 (ranging from 7.98 to 15.16 Tg CH 4 yr −1 ). Among the emissions, 8.11 Tg CH 4 yr −1 (ranging from 5.20 to 11.36 Tg CH 4 yr −1 ) derived from rice paddies, 2.69 Tg CH 4 yr −1 (ranging from 2.46 to 3.20 Tg CH 4 yr −1 ) from natural wetlands, and 0.46 Tg CH 4 yr −1 (ranging from 0.33 to 0.59 Tg CH 4 yr −1 ) from lakes (including reservoirs and ponds). Plentiful water and warm conditions, as well as its large rice paddy area make rice paddies in southeastern C hina the greatest overall source of CH 4 , accounting for approximately 55% of total paddy emissions. Natural wetland estimates were slightly higher than the other estimates owing to the higher CH 4 emissions recorded within Q inghai‐ T ibetan P lateau peatlands. Total CH 4 emissions from lakes were estimated for the first time by this study, with three quarters from the littoral zone and one quarter from lake surfaces. Rice paddies, natural wetlands, and lakes are not constant sources of CH 4 , but decreasing ones influenced by anthropogenic activity and climate change. A new progress‐based model used in conjunction with more observations through model‐data fusion approach could help obtain better estimates and insights with regard to CH 4 emissions deriving from wetlands and lakes in C hina.

Inter-Annual Variations of Methane Emission from an Open Fen on the Qinghai-Tibetan Plateau: A Three-Year Study - Chen, Huai; Wu, Ning; Wang, Yanfen; Zhu, Dan; Zhu, Qiu’an; Yang, Gang; Gao, Yongheng; Fang, Xiuqin; Wang, Xu; Peng, Changhui (PLoS ONE, 2013)

Nitrous oxide emissions from the surface of the Three Gorges Reservoir - Zhu, Dan; Chen, Huai; Yuan, Xingzhong; Wu, Ning; Gao, Yongheng; Wu, Yan; Zhang, Yongmei; Peng, Changhui; Zhu, Qiu’an; Yang, Gang; Wu, Jianghua (Ecological Engineering, 2013)

Soil properties and species composition under different grazing intensity in an alpine meadow on the eastern Tibetan Plateau, China - Yang, Zhen’an; Xiong, Wan; Xu, Yingyi; Jiang, Lin; Zhu, Erxiong; Zhan, Wei; He, Yixin; Zhu, Dan; Zhu, Qiuan; Peng, Changhui; Chen, Huai (Environmental Monitoring and Assessment, 2016)

Carbon dynamics of peatlands in China during the Holocene - Wang, Mei; Chen, Huai; Wu, Ning; Peng, Changhui; Zhu, Qiuan; Zhu, Dan; Yang, Gang; Wu, Jianghua; He, Yixin; Gao, Yongheng; Tian, Jianqing; Zhao, Xinquan (Quaternary Science Reviews, 2014)

Carbon and nitrogen cycling on the Qinghai–Tibetan Plateau - Chen, Huai; Ju, Peijun; Zhu, Qiuan; Xu, Xingliang; Wu, Ning; Gao, Yongheng; Feng, Xiaojuan; Tian, Jianqing; Niu, Shuli; Zhang, Yangjian; Peng, Changhui; Wang, Yanfen (Nature Reviews Earth & Environment, 2022)

The linkage between vegetation and soil nutrients and their variation under different grazing intensities in an alpine meadow on the eastern Qinghai-Tibetan Plateau - Yang, Zhenan; Zhu, Qiuan; Zhan, Wei; Xu, Yingyi; Zhu, Erxiong; Gao, Yongheng; Li, Shiqing; Zheng, Qunying; Zhu, Dan; He, Yixin; Peng, Changhui; Chen, Huai (Ecological Engineering, 2018)

The 5000-year climate change of northeastern Qinghai-Tibetan Plateau and historical ecology of Zoige wetlands - He Yixin, 何奕忻; Wu Ning, 吴宁; Zhu Qiu'an, 朱求安; Chen Huai, 陈槐; Zhu Dan, 朱单; Peng Changhui, 彭长辉; Yang Gang, 杨刚; Gao Yongheng, 高永恒; Zhao Chuan, 赵川 (Acta Ecologica Sinica, 2014)

Higher recent peat C accumulation than that during the Holocene on the Zoige Plateau - Wang, Mei; Yang, Gang; Gao, Yongheng; Chen, Huai; Wu, Ning; Peng, Changhui; Zhu, Qiuan; Zhu, Dan; Wu, Jianghua; He, Yixin; Tian, Jianqing; Zhao, Xinquan; et al. (Quaternary Science Reviews, 2015)

Soil methane uptake by grasslands and forests in China - Wang, Yanfen; Chen, Huai; Zhu, Qiuan; Peng, Changhui; Wu, Ning; Yang, Gang; Zhu, Dan; Tian, Jianqing; Tian, Liuxi; Kang, Xiaoming; He, Yixin; Gao, Yongheng; et al. (Soil Biology and Biochemistry, 2014)

Peatland degradation reduces methanogens and methane emissions from surface to deep soils - Yang, Gang; Tian, Jianqing; Chen, Huai; Jiang, Lin; Zhan, Wei; Hu, Ji; Zhu, Erxiong; Peng, Changhui; Zhu, Qiuan; Zhu, Dan; He, Yixin; Li, Mingxu; et al. (Ecological Indicators, 2019)

Comparison of methane emissions among invasive and native mangrove species in Dongzhaigang, Hainan Island - He, Yixin; Guan, Wei; Xue, Dan; Liu, Liangfeng; Peng, Changhui; Liao, Baowen; Hu, Ji; Zhu, Qiu'an; Yang, Yanzhen; Wang, Xu; Zhou, Guanyi; Wu, Zhongming; et al. (Science of The Total Environment, 2019)

Interannual variation in methane emissions from tropical wetlands triggered by repeated El Niño Southern Oscillation - Zhu, Qiuan; Peng, Changhui; Ciais, Philippe; Jiang, Hong; Liu, Jinxun; Bousquet, Philippe; Li, Shiqin; Chang, Jie; Fang, Xiuqin; Zhou, Xiaolu; Chen, Huai; Liu, Shirong; et al. (Global Change Biology, 2017)
Abstract Methane (CH 4 ) emissions from tropical wetlands contribute 60%–80% of global natural wetland CH 4 emissions. Decreased wetland CH 4 emissions can act as a negative feedback mechanism for future climate warming and vice versa. The impact of the El Niño–Southern Oscillation (ENSO) on CH 4 emissions from wetlands remains poorly quantified at both regional and global scales, and El Niño events are expected to become more severe based on climate models’ projections. We use a process‐based model of global wetland CH 4 emissions to investigate the impacts of the ENSO on CH 4 emissions in tropical wetlands for the period from 1950 to 2012. The results show that CH 4 emissions from tropical wetlands respond strongly to repeated ENSO events, with negative anomalies occurring during El Niño periods and with positive anomalies occurring during La Niña periods. An approximately 8‐month time lag was detected between tropical wetland CH 4 emissions and ENSO events, which was caused by the combined time lag effects of ENSO events on precipitation and temperature over tropical wetlands. The ENSO can explain 49% of interannual variations for tropical wetland CH 4 emissions. Furthermore, relative to neutral years, changes in temperature have much stronger effects on tropical wetland CH 4 emissions than the changes in precipitation during ENSO periods. The occurrence of several El Niño events contributed to a lower decadal mean growth rate in atmospheric CH 4 concentrations throughout the 1980s and 1990s and to stable atmospheric CH 4 concentrations from 1999 to 2006, resulting in negative feedback to global warming.

Effect of Grazing Intensities on Soil N2O Emissions from an Alpine Meadow of Zoige Plateau in China - Zhan, Wei; Yang, Zhenan; Liu, Jianliang; Chen, Huai; Yang, Gang; Zhu, Erxiong; Hu, Ji; Jiang, Lin; Liu, Liangfeng; Zhu, Dan; He, Yixin; Zhao, Chuan; et al. (Atmosphere, 2021)
The alpine meadow of Zoige Plateau plays a key role in local livestock production of cattle and sheep. However, it remains unclear how animal grazing or its intensity affect nitrous oxide (N2O) emissions, and the main driving factors. A grazing experiment including four grazing intensities (G0, G0.7, G1.2, G1.6 yak ha−1) was conducted between January 2013 and December 2014 to evaluate the soil nitrous oxide (N2O) fluxes under different grazing intensities in an alpine meadow on the eastern Qinghai–Tibet Plateau of China. The N2O fluxes were examined with gas collected by the static chamber method and by chromatographic concentration analysis. N2O emissions in the growing seasons (from May to September) were lower than that in non-growing seasons (from October to April) in 2013, 1.94 ± 0.30 to 3.37 ± 0.56 kg N2O ha−1 yr−1. Annual mean N2O emission rates were calculated as 1.17 ± 0.50 kg N2O ha−1 yr−1 in non-grazing land (G0) and 1.94 ± 0.23 kg N2O ha−1 yr−1 in the grazing land (G0.7, G1.2, and G1.6). The annual mean N2O flux showed no significant differences between grazing treatments in 2013. However, there were significantly greater fluxes from the G0.7 treatment than from the G1.6 treatment in 2014, especially in the growing season. Over the two years, the soil N2O emission rate was significantly negatively correlated with soil water-filled pore space (WFPS) and dissolved organic carbon (DOC) content as well as positively correlated with soil available phosphorus (P). No relationship was observed between soil N2O emission rate and temperature or rainfall. Our results showed that the meadow soils acted as a source of N2O for most periods and turned into a weak sink of N2O later during the sampling period. Our results highlight the importance of proper grazing intensity in reducing N2O emissions from alpine meadow. The interaction between grazing intensity and N2O emissions should be of more concern during future management of pastures in Zoige Plateau.

An early warning signal for grassland degradation on the Qinghai-Tibetan Plateau - Zhu, Qiuan; Chen, Huai; Peng, Changhui; Liu, Jinxun; Piao, Shilong; He, Jin-Sheng; Wang, Shiping; Zhao, Xinquan; Zhang, Jiang; Fang, Xiuqin; Jin, Jiaxin; Yang, Qi-En; et al. (Nature Communications, 2023)
Abstract Intense grazing may lead to grassland degradation on the Qinghai-Tibetan Plateau, but it is difficult to predict where this will occur and to quantify it. Based on a process-based ecosystem model, we define a productivity-based stocking rate threshold that induces extreme grassland degradation to assess whether and where the current grazing activity in the region is sustainable. We find that the current stocking rate is below the threshold in ~80% of grassland areas, but in 55% of these grasslands the stocking rate exceeds half the threshold. According to our model projections, positive effects of climate change including elevated CO 2 can partly offset negative effects of grazing across nearly 70% of grasslands on the Plateau, but only in areas below the stocking rate threshold. Our analysis suggests that stocking rate that does not exceed 60% (within 50% to 70%) of the threshold may balance human demands with grassland protection in the face of climate change.

Detecting One-Hundred-Year Environmental Changes in Western China Using Seven-Year Repeat Photography - Chen, Huai; Yin, Kaipu; Wang, Haiyan; Zhong, Shenxian; Wu, Ning; Shi, Fusun; Zhu, Dan; Zhu, Qiuan; Wang, Weifeng; Ma, Zhihai; Fang, Xiuqin; Li, Weizhong; et al. (PLoS ONE, 2011)

Climate-driven increase of natural wetland methane emissions offset by human-induced wetland reduction in China over the past three decades - Zhu, Qiuan; Peng, Changhui; Liu, Jinxun; Jiang, Hong; Fang, Xiuqin; Chen, Huai; Niu, Zhenguo; Gong, Peng; Lin, Guanghui; Wang, Meng; Wang, Han; Yang, Yanzheng; et al. (Scientific Reports, 2016)
Abstract Both anthropogenic activities and climate change can affect the biogeochemical processes of natural wetland methanogenesis. Quantifying possible impacts of changing climate and wetland area on wetland methane (CH 4 ) emissions in China is important for improving our knowledge on CH 4 budgets locally and globally. However, their respective and combined effects are uncertain. We incorporated changes in wetland area derived from remote sensing into a dynamic CH 4 model to quantify the human and climate change induced contributions to natural wetland CH 4 emissions in China over the past three decades. Here we found that human-induced wetland loss contributed 34.3% to the CH 4 emissions reduction (0.92 TgCH 4 ), and climate change contributed 20.4% to the CH 4 emissions increase (0.31 TgCH 4 ), suggesting that decreasing CH 4 emissions due to human-induced wetland reductions has offset the increasing climate-driven CH 4 emissions. With climate change only, temperature was a dominant controlling factor for wetland CH 4 emissions in the northeast (high latitude) and Qinghai-Tibet Plateau (high altitude) regions, whereas precipitation had a considerable influence in relative arid north China. The inevitable uncertainties caused by the asynchronous for different regions or periods due to inter-annual or seasonal variations among remote sensing images should be considered in the wetland CH 4 emissions estimation.

The carbon stock of alpine peatlands on the Qinghai–Tibetan Plateau during the Holocene and their future fate - Chen, Huai; Yang, Gang; Peng, Changhui; Zhang, Yao; Zhu, Dan; Zhu, Qiuan; Hu, Ji; Wang, Mei; Zhan, Wei; Zhu, Erxiong; Bai, Zengzhi; Li, Wei; et al. (Quaternary Science Reviews, 2014)

The impacts of climate change and human activities on biogeochemical cycles on the Q inghai‐ T ibetan P lateau - Chen, Huai; Zhu, Qiuan; Peng, Changhui; Wu, Ning; Wang, Yanfen; Fang, Xiuqing; Gao, Yongheng; Zhu, Dan; Yang, Gang; Tian, Jianqing; Kang, Xiaoming; Piao, Shilong; et al. (Global Change Biology, 2013)
Abstract With a pace of about twice the observed rate of global warming, the temperature on the Qinghai‐Tibetan Plateau (Earth's ‘third pole’) has increased by 0.2 °C per decade over the past 50 years, which results in significant permafrost thawing and glacier retreat. Our review suggested that warming enhanced net primary production and soil respiration, decreased methane ( CH 4 ) emissions from wetlands and increased CH 4 consumption of meadows, but might increase CH 4 emissions from lakes. Warming‐induced permafrost thawing and glaciers melting would also result in substantial emission of old carbon dioxide ( CO 2 ) and CH 4 . Nitrous oxide ( N 2 O ) emission was not stimulated by warming itself, but might be slightly enhanced by wetting. However, there are many uncertainties in such biogeochemical cycles under climate change. Human activities (e.g. grazing, land cover changes) further modified the biogeochemical cycles and amplified such uncertainties on the plateau. If the projected warming and wetting continues, the future biogeochemical cycles will be more complicated. So facing research in this field is an ongoing challenge of integrating field observations with process‐based ecosystem models to predict the impacts of future climate change and human activities at various temporal and spatial scales. To reduce the uncertainties and to improve the precision of the predictions of the impacts of climate change and human activities on biogeochemical cycles, efforts should focus on conducting more field observation studies, integrating data within improved models, and developing new knowledge about coupling among carbon, nitrogen, and phosphorus biogeochemical cycles as well as about the role of microbes in these cycles.